Building A Superior Strategy In The Company Precast Concrete With A Resource Based View Approach (PT. ABX) - Okki Prasetyo; Paulus Wardoyo; Yuli Budiati (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
Abstract This study aims to build a superior strategy in the company precast concrete with a Resource Based View approach at PT. ABX, as well as generate strategies in exploiting resources, capabilities, competitive advantages to create sustainable strategies for the company. The research method used is qualitative based on phenomenology. The research results show that to improve employee performance, it is necessary to carry out work evaluations and targets. Combine the company's human resources and physical resources by placing employees who are competent and experienced in their fields. To increase the knowledge, skills and abilities of employees, companies need to conduct training. To expedite the precast concrete production process, companies need to have a batching plant. Evaluate the production process and routinely carry out material tests and concrete tests to maintain quality and quality. Promotion through digital media, such as Google, websites and other social media. Maintain product quality and quality by using the best quality iron and casting using ready mix. Carrying out product development by innovating molds and precast concrete products to make them more efficient by conducting research on product structure and composition without compromising quality. Improving services and maintaining good relations with consumers and potential customers. Keywords: Resource Based View, Resource, Ability, Competitive Advantage, Strategy